Overload capacity analysis of extra high voltage AC XLPE submarine cable - Zhang, Hao; Ma, Guoqing; Li, Pengfei; Huang, Youcong; He, Tongtong; Zheng, Yuesheng (Frontiers in Energy Research, 2023)
When submarine cable line fails or other lines need load transfer, it often suffers from emergency ampacity that exceeds the steady-state ampacity. The layout environment of the submarine cable is always complex and changeable, and the overload capacity of the submarine cable in different layout environments is also different. Therefore, it is necessary to analyze the overload capacity of the submarine cable. In this paper, a coupled multi-physical field model by finite element method is established for AC 500 kV XLPE extra high voltage submarine cable in landing section, which is the ampacity bottleneck section of the whole line. The overload capacity of submarine cable in two typical layout environments which are direct buried and within pipeline is analyzed. The results show that the overload capacity of submarine cable in the direct buried environment is much higher than that in the pipeline environment. The allowable emergency time in the direct buried environment is 2-3 times that of the pipeline environment under the same condition. In the two typical layout environments, when the emergency current are 2500 A and 3500 A, the ratio of the emergency time allowed to run in the direct buried environment to that in the pipeline environment is about 5 times under the same initial capacity. The proposed model can provide a reference for dynamic capacity control of the extra high voltage submarine cable.